2021
DOI: 10.1186/s12884-020-03508-4
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and neonatal outcomes in women with pregnancy associated cancer: a population-based study in Lombardy, Northern Italy

Abstract: Background Pregnancy associated cancer (PAC) may lead to adverse obstetric and neonatal outcomes. This study aims to assess the association between PACs and adverse perinatal outcomes [i.e. labor induction, iatrogenic delivery, preterm birth, small for gestational age (SGA) newborn, low Apgar score, major malformations, perinatal mortality] in Lombardy, Northern Italy. Methods This population-based historic cohort study used the certificate of deli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
1
11
2
Order By: Relevance
“…Our results confirmed findings from previous studies that infants born to women with PAC are more likely to be born preterm and to be of low birthweight but that there is no significant association between PAC and the odds of a baby being born SGA [ 5 ]. These results suggest that the high prevalence of low birthweight observed in PAC infants is more likely to be due to preterm birth rather than restricted fetal growth.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results confirmed findings from previous studies that infants born to women with PAC are more likely to be born preterm and to be of low birthweight but that there is no significant association between PAC and the odds of a baby being born SGA [ 5 ]. These results suggest that the high prevalence of low birthweight observed in PAC infants is more likely to be due to preterm birth rather than restricted fetal growth.…”
Section: Discussionsupporting
confidence: 91%
“…It is noteworthy that melanoma was the major contributor to diagnoses of PAC in our study cohort. This contrasts previous international studies that report breast cancer as the major contributor to PAC [ 1 , 5 , 8 ] and reflects the overall high incidence of skin cancers in Australia [ 33 ].…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…20 Over 40% of the women with GBC included in this study had a preterm birth. Although this result is marginally lower than rates previously reported in an Italian study (50%) and a retrospective NSW data-linkage study (52%), 9,21 it is more than five times the overall rate of preterm birth in Australia. 22 Our study further revealed that the rate of preterm birth was higher among women who received systemic therapy during pregnancy compared with those who delayed treatment until after birth.…”
Section: Initiation Of Breastfeedingcontrasting
confidence: 74%